Digitalization, Spillover and Environmental, Social, and Governance Performance: Evidence From China - Jiafeng Gu (The Journal of Environment & Development, 2024)
There is growing interest in the relationship between digitalization and environmental, social, and governance (ESG) performance, but existing research focuses on the one-way relationship and ignores the two-way mechanism. Based on a sample of 3335 listed companies in China in 2020, this study adopts a spatial simultaneous equation model to investigate the bidirectional mechanism between companies’ digitalization and ESG performance. The results show that digitalization and ESG performance have a significant positive two-way mechanism; digitalization enhances ESG performance, while ESG performance promotes digitalization. The results also indicate a significant positive intra-industry spillover effect for both digitization and ESG performance. Further research shows that the relationship between digitization and ESG performance does not differ depending on the definition of spatial weights, however, the spillover effects do differ depending on the definition of spatial weights.